On the Second-order Equations of Mixed Type of First Kind (Journal of Partial Differential Equations, 1993)
In this paper the generalized Tricomi problem for the second-order equation of mixed type of first kind is considered. The uniqueness or solutions is proved under very weak conditions oil the coefficients or equation and the boundary curve of domain. The existence of H&sup1 strong solutions is proved for the Tricomi problem.
Keywords: Equation or mixed type; generalized Tricomi problem; strong solution